The Influence of Good Corporate Governance on Sukuk Rating - Retno Puji Astuti (Universitas Mercu Buana, 2020)
This objective of this study to determine the influence of sukuk ratings on corporate governance. Proxy of the corporate governance that used is institutional ownership, frequency of board meeting, board size, and audit committee. The population in this studies are financial and non-financial companies listed on the Indonesia Stock Exchange (IDX), and issue bonds that are rated by PEFINDO in 2012-2017. The research was conducted with quantitative methods. The analysis methods used in this study is multiple linear regression and assisted by SPSS version 20. The results of this research indicate that institutional ownership has significantly positive affect on sukuk rating, frequency of board meeting has insignificantly negative affect on sukuk rating and board size has significantly negative affect on sukuk rating and audit committee has significantly positive affect on sukuk rating..